Green Banking Practices and Perceived Bank Performance: Mediating Role of Green Financing - Thapa , Bharat Singh; Dhakal , Bibek (Journal of Innovation in Academia, 2025)
This study examines the impact of green banking practices (GBP) on perceived bank performance (BP), with a specific focus on the mediating role of green financing (GF). It analyzes four GBP dimensions, namely employee, operation, customer, and policy-related, using data from 269 banking professionals. Results show that GBPs and GF positively affect both environmental and financial performance, with GF partially mediating this relationship. Among GBP components, customer-related practices have the strongest impact, followed by employee and policy-related efforts, while operation-related practices show no significant influence. The findings provide strategic insights for banks and policymakers: strengthening green financing tools, integrating environmental policies into operations, and boosting customer and employee involvement are essential for sustainable outcomes. This study contributes to the evolving discourse on green finance by highlighting actionable pathways for improving both environmental and financial performance in the banking industry.